International society of sports nutrition position stand: caffeine and performance - Goldstein, E.; Ziegenfuss, T.; Kalman, D.; Kreider, R.; Campbell, B.; Wilborn, C.; Taylor, L.; Willoughby, D.; Stout J.; Graves, B. S.; Wildman, R.; Ivy, J. L.; et al. (Journal of the International Society of Sports Nutrition, 2010)
The position of The Society regarding caffeine supplementation and sport performance is summarized by the following seven points: 1.) Caffeine is effective for enhancing sport performance in trained athletes when consumed in low-to-moderate dosages (~3-6 mg/kg) and overall does not result in further enhancement in performance when consumed in higher dosages ( [greater than or equal to] 9 mg/kg). 2.) Caffeine exerts a greater ergogenic effect when consumed in an anhydrous state as compared to coffee. 3.) It has been shown that caffeine can enhance vigilance during bouts of extended exhaustive exercise, as well as periods of sustained sleep deprivation. 4.) Caffeine is ergogenic for sustained maximal endurance exercise, and has been shown to be highly effective for time-trial performance. 5.) Caffeine supplementation is beneficial for high-intensity exercise, including team sports such as soccer and rugby, which is categorized by intermittent activity within a period of prolonged duration. 6.) The literature is equivocal when considering the effects of caffeine supplementation on strength-power performance, and additional research in this area is warranted. 7.) The scientific literature does not support caffeine-induced dieresis during exercise, or any harmful change in fluid balance that would negatively affect performance.